Relationship Between Frailty and Risk of Falls Among Hospitalised Older People with Cardiac Conditions: An Observational Cohort Study. - Rivas-González, Noel; López, María; Martín-Gil, Belén; Fernández-Castro, Mercedes; Castro, María José; San Román, J. Alberto (Nursing Reports, 2025)
Background/Objective: Ageing favours the onset of cardiovascular diseases, frailty, and risk of falls. In the hospital setting, 47.7% of patients may be frail, and the incidence of falls may be as high as five per thousand. This study seeks to determine the relationship between frailty, risk of falls, and length of hospital stays in hospitalised older adults with heart disease. Methods: An observational study was conducted of a cohort of patients aged ≥60 years admitted to a cardiology unit (2022–2024). Frailty was assessed using Fried's phenotype, risk of falls using the J.H. Downton scale, and level of dependency using the Barthel index. Clinical variables, anthropometric measurements, and length of stay were analysed. Statistical analysis: quantitative variables were expressed as means and standard deviations, and categorical variables as frequencies. Associations were analysed using Student's t-tests, chi-squared tests, and Kruskal–Wallis tests for comparisons of three or more groups. Relationships between frailty, risk of falls, and other variables were examined using univariate binary logistic regression, with a 95% confidence interval and statistical significance set at p < 0.05. Results: A total of 144 patients were recruited (mean age = 73.08 years [SD = 7.95]) (women = 33.30%). Frailty was associated with waist circumference in men (p = 0.01) and diastolic blood pressure in women (p = 0.05). Frailty was further linked to Downton scores (odds ratio [OR] = 1.565; 95% CI: 1.156–2.120; p = 0.004), age (OR = 1.114; 95% CI: 1.058–1.173; p = 0.000), Barthel index (OR = 0.902; 95% CI: 0.854–0.953; p = 0.000), and length of stay (OR = 1.101; 95% CI: 1.021–1.186; p = 0.012). Conclusions: Frailty appears to be related to Downton scores and impacts the length of hospital stays in older adults hospitalised with cardiac conditions.